“Sniffing” out SARS-CoV-2 in Arizona working dogs: an exploratory serosurvey - Hecht, Gavriella; Sarbo, Nathan; Svoboda, Wayne; Mead, Heather L.; Ruberto, Irene; Altin, John A.; Engelthaler, David M.; Venkat, Heather; Yaglom, Hayley D. (Frontiers in Veterinary Science, 2023)
Susceptibility to and infection with SARS-CoV-2 in companion animals has been well-documented throughout the COVID-19 pandemic. Surveillance for the virus in dogs has largely been focused on household pets; however, other canine populations may also be impacted. We partnered with a local veterinary hospital with a high working dog patient volume to conduct viral and neutralizing antibody testing in working dogs and identify potential risk factors in the dog's work and home environments. Surveillance of SARS-CoV-2 in law enforcement and security working dogs in Arizona found 24.81% (32/129) of dogs to be seropositive. Thirteen dogs presenting with clinical signs or with reported exposure to COVID-19 in the 30 days prior to sample collection were also tested by PCR; all samples were negative. 90.7% (n=117) of dogs were reported to be asymptomatic or have no change in performance at the time of sampling. Two dogs (1.6%) had suspected anosmia as reported by their handlers; one of which was seropositive. Known exposure to the dog’s COVID-19 positive handler or household member was identified as a significant risk factor. Demographics factors including sex, altered status, and type of work were not associated with canine seropositivity. Further work is warranted to understand the impact of SARS-CoV-2 and other infectious diseases in working dogs.